Student Interest in Standardized Information Services in Higher Education Library - Masriyatun, Masriyatun (Universitas Airlangga, 2024)
Background: Information is a need that must be met for everyone, but information related to standardization is still limited to those who know it. Standardization information is basically information relating to various fields of standardization, such as trade, industry, education and science and technology development. While standardization information services are still rarely performed by the library environment. Methods: This type of research with quantitative descriptive. Sampling technique using random sampling technique, by taking 10% of the total population. Where data collection with a questionnaire. The research subject is student interest in the field of standardization. Purpose: Because standardization information services are not widely known by students, the writer tries to find out the extent of students' interest in standardization information services at the Sebelas Maret University Library, Surakarta. Place of research at UPT Library of Sebelas Maret University Surakarta. Findings: The results obtained show that students' interest in standardization information services can be categorized as moderate as evidenced by the number 44 or 37.9% of students stating that on average they are less interested in standardization information services at the UPT Library of Sebelas Maret University. This is because there has been no socialization regarding the existence of information services in the field of standardization directly at the Sebelas Maret University Library UPT. Conclusion: It is necessary to hold socialization so that information reaches students. Keywords: Student interest, Information Services, and Standardization ————————————————————————————————————- ABSTRAK Minat Mahasiswa terhadap Layanan Informasi Standardisasi di Perpustakaan Perguruan Tinggi Latar Belakang: Informasi merupakan kebutuhan yang harus dipenuhi bagi semua orang, namun informasi yang berkaitan dengan standardisasi masih terbatas orang yang mengenalnya. Informasi standardisasi pada dasarnya informasi yang berkaitan dengan berbagai bidang standardisasi, bisa seperti perdagangan, perindustrian, pendidikan dan pengembangan IPTEK. Sementara layanan informasi standardisasi masih jarang dilakukan oleh lingkungan perpustakaan. Metode: Jenis penelitian adalah deskriptif kuantitatif. Teknik pengambilan sampel menggunakan teknik random sampling, dengan pengambilan sampel 10% dari jumlah populasi. Dimana pengambilan data menggunakan kuesioner. Subyek penelitian adalah minat mahasiswa terhadap bidang standardisasi. Tujuan: Karena layanan informasi standardisasi belum banyak dikenal oleh mahasiswa sehingga penulis mencoba ingin mengetahui sejauh mana “Minat Mahasiswa terhadap Layanan Informasi Standardisasi melalui Portal SNI Corner di UPT Perpustakaan Universitas Sebelas Maret Surakarta.” Tempat penelitian di UPT Perpustakaan Universitas Sebelas Maret Surakarta. Temuan: Hasil yang didapatkan bahwa minat mahasiswa terhadap layanan informasi standardisasi dapat dikategorikan sedang yang dibuktikan dengan angka 44 atau 37,9 % mahasiswa menyatakan rata-rata kurang berminat akan layanan informasi bidang standardisasi di UPT Perpustakaan Universitas Sebelas Maret. Hal ini dikarenakan belum adanya sosialisasi mengenai layanan informasi bidang standardisasi secara langsung di UPT Perpustakaan Universitas Sebelas Maret. Kesimpulan: Perlunya diadakan sosialisasi agar informasi mengenai bidang standardisasi di UPT Perpustakaan Universitas Sebelas Maret dapat tersampaikan ke mahasiswa. Kata Kunci: Minat mahasiswa, Layanan Informasi, dan Standardisasi